A new genus and ten new species of spiders (Arachnida, Araneae) from Iran - Alireza Zamani; Yuri M. Marusik (ZooKeys, 2021)
One new genus (Sestakovaia gen. nov.; Liocranidae) and 10 new species of five families of spiders are described from different provinces of Iran: Brigittea avicenna sp. nov. (♂♀, Alborz and Kurdistan provinces) (Dictynidae), Micaria atropatene sp. nov. (♂, East Azerbaijan Province), Zagrotes borna sp. nov. (♂, Hormozgan Province), Z. parla sp. nov. (♂, Kerman Province) (Gnaphosidae), Sestakovaia hyrcania sp. nov. (♂, Golestan Province), Mesiotelus patricki sp. nov. (♂, Golestan Province) (Liocranidae), Palpimanus carmania sp. nov. (♂, Kerman Province), P. persicus sp. nov. (♂♀, Hormozgan Province) (Palpimanidae), Rhysodromus genoensis sp. nov. (♂, Hormozgan Province), and R. medes sp. nov. (♂, Hormozgan Province) (Philodromidae). Furthermore, Sestakovaia annulipes (Kulczyński, 1897), comb. nov. (ex. Mesiotelus) and Zagrotes bifurcatus (Zamani, Chatzaki, Esyunin & Marusik, 2021), comb. nov. (ex. Berinda) are proposed as new combinations.